Response of Plants to Water Stress: A Meta-Analysis - Sun, Yuan; Wang, Cuiting; Chen, Han Y. H.; Ruan, Honghua (Frontiers in Plant Science, 2020)
Plants are key to the functionality of many ecosystem processes. The duration and intensity of water stress are anticipated to increase in the future; however, an elucidation of the responses of plants to water stress remains incomplete. For this study, we present a global meta-analysis derived from 1301 paired observations from 84 studies to evaluate the response patterns and mechanisms of plants to water stress. The results revealed that while water stress inhibited plant growth and photosynthesis, reactive oxygen species (ROS), plasma membrane permeability, enzymatic antioxidants, and non-enzymatic antioxidants increased. These responses generally increased with the intensity of water stress but were mitigated with experimental duration. Our findings suggested that the overproduction of ROS was the primary mechanism of plants in response to water stress and that plants tend to acclimate to water stress over time to some extent. Our synthesis provides a framework for understanding the responses and mechanisms of plants under drought conditions.